Dissociable Neural Correlates of Intention and Action Preparation in Voluntary Task Switching. (26th October 2012) - Poljac, Edita; Yeung, Nick
Abstract : This electroencephalographic (EEG) study investigated the impact of between-task competition on intentional control in voluntary task switching. Anticipatory preparation for an upcoming task switch is a hallmark of top-down intentional control. Meanwhile, asymmetries in performance and voluntary choice when switching between tasks differing in relative strength reveal the effects of between-task competition, reflected in a surprising bias against switching to an easier task. Here, we assessed the impact of this bias on EEG markers of intentional control during preparation for an upcoming task switch. The results revealed strong and varied effects of between-task competition on EEG markers of global task preparation—a frontal contingent negative variation (CNV), a posterior slow positive wave, and oscillatory activity in the alpha band (8–12 Hz) over posterior scalp sites. In contrast, we observed no between-task differences in motor-specific task preparation, as indexed by the lateralized readiness potential and by motor-related amplitude asymmetries in the mu (9–13 Hz) and beta (18–26 Hz) frequency bands. Collectively, these findings demonstrate that between-task competition directly influences the formation of top-down intentions, not only their expression in overt behavior. Specifically, this influence occurs at the level of global task intention rather than the preparation of specific actions.